Mental health, race, and police contact: intersections of risk and trust in the police. Issue 4 (21st November 2016) - Thompson, Melissa; Kahn, Kimberly Barsamian
Abstract : Purpose: The purpose of this paper is to understand whether mental health status – either alone or in conjunction with race – affects perceptions of police legitimacy. Design/methodology/approach: Using survey data collected from Portland, Oregon residents ( n =259), this research examines predictors of trust in the police. Findings: Results show that individuals with a history of mental illness are similar to African-American respondents: both are especially distrustful of the police. The combination of race and mental illness does not appear to create additional levels of distrust. Social implications: This research suggests there are important racial and mental health disparities in perceived police legitimacy, and that these disparities will need to be addressed for the police to successfully combat crime and encourage compliance with the law. Originality/value: Although research has consistently highlighted how race affects perceptions of police legitimacy, research has not yet examined whether mental health status affects perceptions of police legitimacy; in addition to race, this paper highlights the unique perspectives of individuals with mental health concerns regarding policing.